Development of a Student Worksheet Based on a Three-Dimensional Thinking Graph to Support Students’ Critical Thinking Skills - Nia Diniati; Afrida Afrida; Asmiyunda Asmiyunda; Kriswantoro Kriswantoro; Febbry Romundza (Jurnal Pijar MIPA, 2026)
Chemical bonding is a fundamental topic in chemistry that is often considered abstract and difficult for students to understand, resulting in low critical thinking skills. The lack of interactive and technology-based teaching materials further exacerbates this problem. Therefore, this study aims to develop an electronic student worksheet based on the Three-Dimensional Thinking Graph on chemical bonding and determine its feasibility in supporting students' critical thinking skills. This study uses the Research and Development (R&D) method with the ADDIE model limited to the analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, questionnaires, expert validation sheets, teacher assessments, and student responses. The product was validated by two validators, material and media experts, and one expert in learning design and Problem-Based Learning. The product trial involved 10 students from class XII F1B at SMAN 11 Muaro Jambi, conducted through one-to-one and small-group tests. Data analysis techniques used percentage analysis and qualitative descriptive analysis. The results showed that the electronic student worksheet obtained a validation score of 92% from material and media experts and 88.57% from learning design experts, with the category of very feasible. Teacher assessments reached 91% and student responses were 86%, categorized as very good. The novelty of this research lies in the integration of concept maps, data tables, and reasoning maps in an interactive electronic student worksheet based on TDTG to systematically support the development of students' critical thinking skills. Thus, the developed electronic student worksheet is deemed feasible and has the potential to support more interactive and meaningful learning of chemical bonds.